PENGARUH PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP INTENSI PEMBELIAN ONLINE PADA PANDEMI DAN KEPERCAYAAN SEBAGAI VARIABEL MODERATING DI MASYARAKAT SUMBAWA - Muhammad Nur Fietroh (UNIVERSITAS KARIMUN, 2023)
This study aims to examine the effect of price and product perceptions on online purchase intentions with trust as a moderating variable in the Sumbawa community. The number of population in this study is unknown. Sampling method using purposive sampling method with a total sample of 100 respondents. Retrieval of data using a questionnaire distributed using the Google form. The data analysis technique used is SEM. The results of this study indicate that price perceptions, products quality have a positive effect on online buying interest and trust can mediate price perception and product quality on online buying interest in the people of Sumbawa.